Enteral micronutrient supplementation and neurodevelopmental outcomes in preterm or low birth weight infants: A systematic review and meta‐analysis - Yakun Liu; Shaobin Jin; Guoqing Zhang; Tingwei Chen; Shungen Huang (Maternal and Child Nutrition)
Abstract The association of enteral micronutrient supplementation and the neurodevelopmental outcomes of preterm or low birth weight (LBW) infants is controversial. This research was prospectively registered (CRD42023454034). We searched MEDLINE, Embase, PsycInfo, ClinicalTrials. gov, and the Cochrane Library for randomised clinical trials (RCTs) or quasi‐RCTs comparing any enteral micronutrients supplementation with placebo or no supplementation in preterm or LBW infants. The primary outcome was neurodevelopmental impairment (NDI), with secondary outcomes involving various neurodevelopmental tests and disabilities. There was no evidence of an association between enteral micronutrients supplementation and the risk of NDI (RR, 1.03; 95% CI, 0.93–1.14; moderate certainty evidence). There was no evidence that the supplemented groups enhanced cognitive (MD, 0.65; 95% CI, −0.37 to 1.67; low certainty evidence), language (SMD, −0.01; 95% CI, −0.11 to 0.09; moderate certainty evidence), or motor scores (SMD, 0.04; 95% CI, −0.06 to 0.15; very low certainty evidence) or IQ (SMD, −0.20; 95% CI, −0.53 to 0.13; very low certainty evidence). Subgroup analysis showed that multiple micronutrients supplementation improved expressive language score (MD, 1.42; 95% CI, 0.39–2.45), and zinc supplementation enhanced fine motor score (SMD, 1.70; 95% CI, 0.98–2.43). The overall heterogeneity was low. This study demonstrates that enteral micronutrient supplementation is associated with little or no benefits in neurodevelopmental outcomes for preterm or LBW infants. Well‐designed RCTs are needed to further ascertain these associations.